Temporal Aspects of Surface Water Quality Variation Using Robust Statistical Tools - Adamu Mustapha; Ahmad Zaharin Aris; Mohammad Firuz Ramli; Hafizan Juahir (The Scientific World Journal)
Robust statistical tools were applied on the water quality datasets with the aim of determining the most significance parameters and their contribution towards temporal water quality variation. Surface water samples were collected from four different sampling points during dry and wet seasons and analyzed for their physicochemical constituents. Discriminant analysis (DA) provided better results with great discriminatory ability by using five parameters with (P<0.05) for dry season affording more than 96% correct assignation and used five and six parameters for forward and backward stepwise in wet season data with P-value (P<0.05) affording 68.20% and 82%, respectively. Partial correlation results revealed that there are strong (rp=0.829) and moderate (rp=0.614) relationships between five-day biochemical oxygen demand (BOD5) and chemical oxygen demand (COD), total solids (TS) and dissolved solids (DS) controlling for the linear effect of nitrogen in the form of ammonia (NH3) and conductivity for dry and wet seasons, respectively. Multiple linear regression identified the contribution of each variable with significant values r = 0.988, R2 = 0.976 and r = 0.970, R2 = 0.942 (P<0.05) for dry and wet seasons, respectively. Repeated measure t-test confirmed that the surface water quality varies significantly between the seasons with significant value P<0.05.